Antibiofilm and Anti-Infection of a Marine Bacterial Exopolysaccharide Against Pseudomonas aeruginosa - Wu, Shimei; Liu, Ge; Jin, Weihua; Xiu, Pengyuan; Sun, Chaomin (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa is a well-known pathogenic bacterium that forms biofilms and produces virulence factors, thus leading to major problems in many fields, such as clinical infection, food contamination and marine biofouling. In this study, we report the purification and characterization of an exopolysaccharide EPS273 from the culture supernatant of marine bacterium Pseudomonas stutzeri 273. The exopolysaccharide EPS273 not only effectively inhibits biofilm formation but also disperses preformed biofilm of Pseudomonas aeruginosa PAO1. High performance liquid chromatography traces of the hydrolyzed polysaccharides shows that EPS273 primarily consists of glucosamine, rhamnose, glucose and mannose. Further investigation demonstrates that EPS273 reduces the production of the virulence factors pyocyanin, exoprotease and rhamnolipid, and the virulence of P. aeruginosa PAO1 to human lung cells A549 and zebrafish embryos is also obviously attenuated by EPS273. In addition, EPS273 also greatly reduces the production of hydrogen peroxide (H2O2) and extracellular DNA (eDNA), which are important factors for biofilm formation. Furthermore, EPS273 exhibits strong antioxidant potential by quenching hydroxyl and superoxide anion radicals. Notably, the antibiofouling activity of EPS273 is observed in the marine environment up to two weeks according to the amounts of bacteria and diatoms in the glass slides submerged in the ocean. Taken together, the properties of EPS273 indicate that it has a promising prospect in combating bacterial biofilm-associated infection, food-processing contamination and marine biofouling.